The role of machine learning in advancing financial technology - Galikyzy, N. (Академик Е.А.Бөкетов атындағы Қарағанды университетінің баспасы, 2024)
Fintech or financial technology applies modern technology to financial services to improve or automate banking and investing activities. Machine learning is useful in parsing the immense amount of information that is consistently and readily available in the world to assist in decision making. In FinTech it is a critical enabler in tech-driven banking, where efficiency and innovation are key to staying ahead of the competition.
Keywords: financial technology; machine learning; trend; investment activity; banking activities